Environmental Conservation Education in a Spatial Approach and Local Wisdom at Trisik Beach, Yogyakarta - Sasongko, Yohanes Probo Dwi; Setyawan, Erwin; Herlina, Herlina (Universitas Negeri Padang, 2025)
The educational activities aimed at tourists and the community in the “Trisik Release Tukik” event broadly aim to introduce a spatial approach to disaster mitigation and environmental conservation education based on local wisdom to tourists visiting Trisik Beach. The activities, which were carried out from July to August, involved the community and stakeholders, including community organizations such as Pokdarwis Banaran. The methods used were qualitative, with traditional lectures supported by visual media and presentations accompanied by narratives of local wisdom. The activities took place in a fun and educational atmosphere, accompanied by question and answer sessions and interactive discussions. The results of the study show that the educational process carried out to build high awareness and understanding in all aspects, especially in applying knowledge in the context of real life to the environment, is a form that must be applied sustainably. The spatial approach makes it easier for visitors to understand locations that are prone to natural disasters and require regular management. Meanwhile, local values strengthen the relationship between visitors and the local social and cultural environment. The non-formal educational approach is a simple, adaptive, and implementable measure in every coastal tourist area by optimizing the use of technology. These findings fully support the effectiveness of the spatial-cultural approach as a relevant, grounded, and widely replicable model for achieving the goals of disaster mitigation education and environmental conservation in other areas with similar tourist attraction characteristics.